De la forma a la estructura en tecnología lítica: una nueva metodología para los Andes Centrales (Perú) - Pérez-Balarezo, Antonio (2025)
This article presents a methodology for the technostructural analysis of carved lithic artifacts that aims to understand how tools were used in the past. The proposal is based on the premise that all tools are a threefold structured system that comprises three parts: transformative, prehensility and energy reception. An artifact belonging to the lithic assemblage recovered at the site of Vadopampa in Ayacucho, Peru, has been analysed with the help of students as an example of the application of the technostructural approach. The paper thus introduces a new methodology for the Central Andes in a didactic and critical way, promotes a dynamic perspective for lithic tools, and assesses the potential and the limits of all technological interpretations.